Професійне інформування як елемент профорієнтаційної роботи польських та українських ВНЗ: порівняльний аспект = Professional awareness as part of the professional work of Polish and Ukrainian Universities: a comparative aspect - Oksana Hudkova; Yuliya Maslova; Walery Zukow (Kazimierz Wielki University, 2016)
Hudkova Oksana, Maslova Yuliya, Zukow Walery. Професійне інформування як елемент профорієнтаційної роботи польських та українських ВНЗ: порівняльний аспект = Professional awareness as part of the professional work of Polish and Ukrainian Universities: a comparative aspect. Journal of Education, Health and Sport. 2016;6(5):316-328. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53121 http://ojs.ukw.edu.pl/index.php/johs/article/view/3532     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   ПРОФЕСІЙНЕ ІНФОРМУВАННЯ ЯК ЕЛЕМЕНТ ПРОФОРІЄНТАЦІЙНОЇ РОБОТИ ПОЛЬСЬКИХ ТА УКРАЇНСЬКИХ ВНЗ: ПОРІВНЯЛЬНИЙ АСПЕКТ Professional awareness as part of the professional work of Polish and Ukrainian Universities: a comparative aspect   Гудкова Оксана Анатоліївна Hudkova Oksana Anatoliyivna Національний університет «Острозька академія» National University "Ostrog Academy"   Маслова Юлія Петрівна Maslova Yuliya Petrivna Національний університет «Острозька академія» National University "Ostrog Academy"   Zukow Walery Zukow Walery UMK w Toruniu UMK in Torun       У статті йдеться про профорієнтаційну роботу серед абітурієнтів польського та українського ВНЗ у порівняльному аспекті. Зокрема, досліджено основні джерела отримання абітурієнтами інформації про ВНЗ, засоби комунікації та рівень задоволеності респондентів обраним ВНЗ.   Ключові слова: профорієнтаційна робота, випускник старшої школи (абітурієнт), джерела інформації, професійне інформування, засоби комунікацій.   The article talks about vocational work among the students of Polish and Ukrainian Universities in comparative aspect. In particular, it examined the main source of getting us information about universities, means of communication and the level of satisfaction of respondents selected universities.   Keywords: vocational work, graduate from senior school (the applicant), sources of information, professional awareness, means of communication.